PENGARUH GAYA HIDUP DENGAN KUALITAS HIDUP LANSIA DI PANTI WREDHA WONOGIRI - Purwandari, Kristiana Puji; Handono, Nugroho Priyo (Akademi Keperawatan Giri Satria Husada Wonogiri, 2019)
A healthy lifestyle describes daily behavior patterns that lead to efforts to maintain a positive physical, mental, social condition. A healthy lifestyle includes sleeping, eating, weight control, not smoking, or drinking alcohol, exercising regularly and being skilled in managing stress experienced by Lisnawati (2006). This study aims to analyze the effect of lifestyle (physical activity, nutrition / diet, sleep rest, behavior) on the health status of the elderly at the Wredha Wonogiri Home. The method used in this research is descriptive research method conducted at the Wredha Wonogiri Home. Descriptive research design, namely research conducted to present a complete description of data and picture of the lifestyle of the elderly using a questionnaire. This study used a survey method approach, namely to collect extensive and large factual data. In this study, the data collection tool was a questionnaire. This questionnaire is defined as a well-structured list of questions, where respondents only need to provide answers or provide certain signs. The results of statistical data processing show that 14 respondents (100%) have a good quality of life. The lifestyle of the elderly at the Wredha Home is classified as good because it is found that a high percentage indicates that the elderly with good physical activity, good diet / nutrition, good resting patterns, and good behavior so that they have a good quality of life as well. This fairly good physical activity shows that the elderly take walks outside the home, light exercise, perform worship, sweep, mop, wash dishes, wash clothes, sunbathe, and breathe fresh air. For diet or nutrition, the elderly at the Wredha Home receive nutritious and balanced food intake. By eating fruits, drinking 8 glasses of water, drinking tea and drinking milk. Fulfillment of the need for sleep rest for the elderly in Wredha orphanage shows a high percentage of the need for sleep rest both during the day and at night. The elderly also have time such as recreation by watching television and reading newspapers or books. The behavior of the elderly, such as praying, surrendering, fasting on certain days shows a high percentage so that it provides a sense of security, reduces anxiety and loneliness felt by the elderly.